Development progeria the role of institutions and the exchange rate - Daway, Sarah Lynne S.; Fabella, Raul V. (2015)
Convergence is more the exception than the rule in the development landscape. As a possible explanation, we posit development progeria: the phenomenon where a low-income country exhibits the industrial share dynamics of high-income mature economies where the Non-traded Goods Sector outgrows the Traded Goods Sector and the share of the non-traded goods sector outstrips the share of the traded goods sector. We argue that this seems to be the case of the Philippines in the last 25 years.

We then inquire into the drivers of this phenomenon. One possibility is the Rodrik hypothesis: that market and institutional distortions hamstring the Tradable goods sector more than they do the Non-tradable goods sector. The other possibility is the exchange rate policy being favorable or unfavorable to the Tradable goods sector. Using cross-country data for countries with per capita income of us$10,000 or less, we show that these two factors cannot be rejected as drivers of development progeria.
Keywords: Economic development